2018
DOI: 10.1101/453563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N-terminal β-strand underpins biochemical specialization of an ATG8 isoform

Abstract: ATG8 is a highly-conserved ubiquitin-like protein that modulates autophagy pathways by binding autophagic membranes and numerous proteins, including cargo receptors and core autophagy components. Throughout plant evolution, ATG8 has expanded from a single protein in algae to multiple isoforms in higher plants. However, the degree to which ATG8 isoforms have functionally specialized to bind distinct proteins remains unclear. Here, we describe a comprehensive proteinprotein interaction resource, obtained using i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…As shown in our phylogenetic tree, nine Arabidopsis proteins were grouped with Atg8 cluster into two groups (Atg8H-I and Atg8A-G), with latter dividing further into two subgroups. In a recent study, potato Atg8 isoforms were also proposed to bind to a distinct set of proteins [44]. The recognition motif for subfamilies, identified in our study, thus also provides a valuable resource for the autophagic community to decode variability within the multi-member Atg8 family.…”
Section: Role Of Evolutionary Constraintssupporting
confidence: 51%
“…As shown in our phylogenetic tree, nine Arabidopsis proteins were grouped with Atg8 cluster into two groups (Atg8H-I and Atg8A-G), with latter dividing further into two subgroups. In a recent study, potato Atg8 isoforms were also proposed to bind to a distinct set of proteins [44]. The recognition motif for subfamilies, identified in our study, thus also provides a valuable resource for the autophagic community to decode variability within the multi-member Atg8 family.…”
Section: Role Of Evolutionary Constraintssupporting
confidence: 51%
“…The methodology used has already been described in earlier studies (Qiao et al, 2016; Wissel et al, 2016; Zess et al, 2018). In brief, the UltiMate 3000 RSLC nano system (Thermo Fisher Scientific, Amsterdam, Netherlands) was combined with Q Exactive HF mass spectrometer (Thermo Fisher Scientific, Bremen, Germany), using a Proxeon nanospray source (Thermo Fisher Scientific, Odense, Denmark).…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description is available in previous articles (Qiao et al, 2016; Wissel et al, 2016; Zess et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is technically challenging and time consuming to generate an Arabidopsis mutant lacking multiple AtATG8 s by conventional genetic mutation, crossing and screening. Recently, Zess et al () employed immunoprecipitation together with mass spectrometry analysis to demonstrate that ATG8 isoforms actually bind to different sets of interactors via their specific N‐terminal β‐strand in potato ( Solanum tuberosum ). Moreover, it was found that diverse populations of transcription factors that are involved in plant development and stress responses bind and regulate the transcription of distinct AtATG8 s in Arabidopsis (Wang et al , ).…”
Section: Autophagy‐related Proteins In Plant Reproductionmentioning
confidence: 99%